Obesity in children with developmental and/or physical disabilities. Issue 3 (July 2015) - Bandini, Linda; Danielson, Melissa; Esposito, Layla E.; Foley, John T.; Fox, Michael H.; Frey, Georgia C.; Fleming, Richard K.; Krahn, Gloria; Must, Aviva; Porretta, David L.; Rodgers, Anne Brown; Stanish, Heidi; et al.
Abstract: Children with developmental or physical disabilities, many of whom face serious health-related conditions, also are affected by the current obesity crisis. Although evidence indicates that children with disabilities have a higher prevalence of obesity than do children without disabilities, little is known of the actual magnitude of the problem in this population. To address this concern, the Eunice Kennedy Shriver National Institute of Child Health and Human Development (NICHD) held a conference on obesity in children with intellectual, developmental, or physical disabilities, bringing together scientists and practitioners in the fields of obesity and disability to foster collaboration, identify barriers to healthy weight status in populations with disabilities, propose avenues to solutions through research and practice, and develop a research agenda to address the problem. This article describes current knowledge about prevalence of obesity in this population, discusses factors influencing obesity risk, and summarizes recommendations for research presented at the conference.